Preface - Šeškauskienė, Inesa; Žeimantienė, Vaiva (Kalbotyra, 2008)
This volume includes articles based on linguistic papers given at the International Conference marking the 40th anniversary of the Department of English Philology and the Department of German Philology of Vilnius University held 18-20 September 2008. The articles cover a large variety of linguistic topics ranging from theoretical to applied, from historical to contemporary dimensions of language study. Many linguists seem to give preference to the contrastive axis of study which often offers a framework of research opening a multitude of vistas onto the same data or phenomena. We are grateful to all contributors of the volume: guests of the Conference, teachers and doctoral students of the Department of English Philology and the Department of German Philology. Our special thanks go to our Teachers—professors of the Departments who worked in the Departments in the years of Soviet occupation and whose dedication and energy made this anniversary a reality. We are also grateful to the sponsors of the Conference without whose generosity the event would have been impossible: the Lithuanian Foundation for Culture at the Ministry of Culture, Emmy Huetemann Fund, the Embassy of Austria in Lithuania, UAB Alumnus, VU Faculty of Philology, VU Saturday School of English and VU Department of Translation Studies.